Evidence for Coupling of the Carbon and Phosphorus Biogeochemical Cycles in Freshwater Microbial Communities - Anderson, O. Roger (Frontiers in Marine Science, 2018)
Considerable attention has been given to the roles of the carbon and phosphate cycles in aquatic environments, but less attention has been given to an experimental analysis of the coupling of the C and P cycles in freshwater and marine ecosystems. Using laboratory microcosm experiments, prepared with natural pond-water microbial communities, evidence is presented for the coupling of dissolved organic C with microbial production of alkaline phosphatase driving the phosphorus cycle in freshwater microbial communities. The effects of glucose C-supplementation in microcosm microbial communities (including bacteria and heterotrophic nanoflagellates) on gains in microbial C-content and alkaline phosphatase activity (APA) were estimated in relation to control microcosms without C-supplementation. The C-supplementation increased total microbial APA (pmol min-1 µg-1 bacterial C) in the C-supplemented treatment (6.5 ± 0.6) compared to the non-supplemented cultures (5.1 ± 1.7). Microbial-bound APA in the C-supplemented treatment was particularly enhanced (4.4 ± 0.9) compared to control cultures (1.3 ± 0.8), but the amount of free (soluble) APA in the aquatic phase was less compared to the controls (n = 5, p < 0.001). Alkaline phosphatase activity was highly correlated (r = 0.97) with bacterial densities in the C-supplemented cultures, further supporting the hypothesis that C-supplementation can increase phosphorus remineralization through elevated production of microbial alkaline phosphatase. This laboratory-based, experimental study suggests that additional research on the coupling of the C and P cycles in freshwater and marine environments may yield productive insights into the finer details of the roles of these two biogeochemical cycles in aquatic microbial community dynamics.